Kajian Life Cycle Assessment Proses Produksi Dore Bullion Pertambangan Emas di Jawa Barat - Rizal Hardiansyah; Adhi Yuniarto; Syaiful Habib; Eva Roslina Sari (Jurnal Serambi Engineering, 2024)
Gold is one of the largest mining products in Indonesia, amounting to 34,39 tons in 2022. In addition, gold is considered to be one of the safest investment instruments currently. The main raw material for gold production is dore bullion, namely metal bars containing gold and silver. Dore bullion production has various impacts on Life Cycle Assessment (LCA) studies. High levels of dore bullion production cause high use of fuel, energy, raw materials, and emissions, so it is necessary to analyze and identify the impact of the precious metal production process using the LCA method. The impacts produced in this research are midpoint and endpoint impacts based on the ReCiPe 2016 (H) method for the cradle-to-gate scope. This LCA study examined 14 midpoint and 3 endpoint impacts. The dominant midpoint impact results are mineral resource scarcity (149,581,850,000 kg Cu eq), water consumption (167.905,36 m3), and global warming (4.514.295,80 kg CO2 eq), while the endpoint impacts are resources (34.608.348.000 USD2013), human health (4,7626 DALY), and ecosystem quality (0,0150 species.yr). The largest impact contributors were the drilling process unit (mineral resource scarcity), milling process unit (water consumption), and dewatering process unit (global warming).